Pengaruh Rendahnya Pemahaman Fungsi Manajemen SDM, Terhadap Kinerja Karyawan: (Studi Kasus Yayasan Al-Ghufron Pamekasan) - Akhmad Fawaid; Fahrurozi Fahrurozi (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2020)
The low understanding of the functions of Human Resources management, affects the weak performance of employees. As a result, it has an impact on the wheels of the organization in the Al-Ghufron Pamekasan Foundation. So to find out how much, the effect caused, research needs to be done. This study uses a qualitative descriptive method. As a result, many employees do not understand the HR function. So, it needs to be equipped with education or training on an ongoing basis, in order to improve the quality of work.